FRI0445 Can Colour-Doppler Sonography of Temporal Arteries Replace Temporal Artery Biopsy in Patients Suspect of Having GIANT Cell Arteritis in Daily Clinical Practice?. (10th June 2014) - Praprotnik, S.; Hočevar, A.; Rotar, Ž.; Tomšič, M.
Abstract : Background: Giant cell arteritis (GCA) is the most common systemic vasculitis in patients over 50 years of age. Recently, the Colour-Doppler Sonography of temporal arteries (CDS-TA) has gained momentum as a potential non-invasive tool for diagnosing GCA.(1, 2) Objectives: To evaluate the diagnostic value of CDS-TA in suspected GCA cases in daily clinical practice. Methods: Subjects with suspected GCA underwent CDS-TA prior to temporal artery biopsy (TAB) and glucocorticoid treatment. TAs and their branches were assessed in longitudinal and transversal planes. The "halo sign" (dark hypo echoic circumferential wall thickening), stenosis or occlusion were considered a positive finding. In addition to CDS-TA, clinical examination, extensive laboratory work-up, and TAB were performed. Diagnosis was established in accordance with the American College of Rheumatology (ACR) criteria for the classification of GCA. Results: From September 2011 to December 2013 94 subjects with suspected GCA were identified. GCA was diagnosed in 56 subjects (59.6%). The remaining 38 subjects (40.4%) who were not diagnosed with GCA served as controls. CDS-TA was performed in 93 subjects (55/56 GCA patients and in 38/38 controls). The characteristic "halo sign" was observed in 44 (80%) of GCA patients and in none of the controls. The "halo sign" was unilateral in 19 (34.5%) and bilateral in 25 (45.5%) of GCA patients. Mean TA wall thickness of the affected vessels was 0.74±0.019 mm vs. 0.27±0.007 mm of the unaffected vessels. Stenoses were found in 28 (50.9%) of GCA patients and in 2 (5.3%) controls. TA occlusion was demonstrated in 6 (10.9%) of GCA patients and in none of the controls. In our population the CDS-TA had an estimated diagnostic sensitivity of 80.0% and specificity of 94.7% with diagnosis based on the ACR criteria serving as a gold standard. A positive CDS-TA had 95.6% positive and 76.6% negative predictive value for GCA. The TAB for the same group had a diagnostic sensitivity of 79.2% and specificity of 88.5%; and a 92.7% positive and a 69.7% negative predictive value. Matching of results from CDS-TA and TAB is shown in Table 1 . In comparison, the patients with GCA with a positive CDS-TA vs those with negative CDS-TA the former had more often had clinically (75.0% vs 27.3%; p=0.003) and histologically (86.5% vs. 50%; p=0.01) altered TAs, jaw claudication (36.4% vs. 9.1%; p=0.08) as well as longer time from the onset of symptoms to diagnosis (8.3 vs. 4.5 weeks, p=0.25) Conclusions: The diagnostic sensitivity and specificity of CDS-TA for diagnosing GCA is comparable, if not superior to TAB. In case of characteristic sonographic changes, CDS-TA may obviate the need for TAB. References: Arida A, Kyprianou M, Kanakis M, Sfikakis PP. The diagnostic value of ultrasonography-derived edema of the temporal artery wall in giant cell arteritis: a second meta-analysis. BMC Musculoskelet Disord 2010;11:44. Diamantopoulos AP, Haugeberg G, Hetland H, Soldal DM, Bie R, Myklebust G. Diagnostic value of color Doppler ultrasonography of temporal arteries and large vessels in giant cell arteritis: a consecutive case series. Arthritis Care Res (Hoboken) 2014;66:113-9. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1967